2011
DOI: 10.1080/04419057.2011.630789
|View full text |Cite
|
Sign up to set email alerts
|

Football fandom, social inclusion and learning disability: opportunities and constraints

Abstract: In Britain, within the contemporary drive to use sport to tackle the isolation of socially excluded groups, football (soccer) fandom has been suggested in many policy documents as a possible site for enabling people with learning disabilities to become more socially included. Forming the basic theoretical work for my doctoral research, this paper provides a critical analysis of this so far unexamined discourse. Conclusions suggest that current policy represents a simplistic and overly romanticised view of peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In that respect, this article specially contributes to the research by ParamioSalcines et al (2014ParamioSalcines et al ( , 2016 and Southby (2011Southby ( , 2013 in that we have added the voices of the customers (i.e. the disabled supporters) to the mix.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In that respect, this article specially contributes to the research by ParamioSalcines et al (2014ParamioSalcines et al ( , 2016 and Southby (2011Southby ( , 2013 in that we have added the voices of the customers (i.e. the disabled supporters) to the mix.…”
Section: Resultsmentioning
confidence: 99%
“…It is considered essential, but 'not sufficient'. Our literature review revealed that this focus on physical barriers is the most commonly used by football clubs (Southby, 2011).…”
Section: Beyond the Status-quo: Access And Informationmentioning
confidence: 99%
See 1 more Smart Citation